Effect of ions on conductivity and permittivity in the Polar Mesosphere Summer Echoes region. Issue 2 (13th April 2021) - Ullah, Safi; Li, HaiLong; Rauf, Abdur; Meng, Lin; Wang, Bin; Ge, ShuCan; Wang, MaoYan
Abstract: For the first time, the effect of ions on complex conductivity and permittivity of dusty plasma at Polar Mesosphere Summer Echoes (PMSE) altitude is analyzed. Because of ions higher mass and smaller thermal velocity, generally, their effects are not considered in the study of electromagnetic properties of dusty plasmas. In this study, we modified the equations of conductivity and permittivity by adding the effect of ions. In the PMSE altitude region between 80 and 90 km, a local reduction in electron density (i.e., an electron bite‐out), is produced by electron absorption onto dust particles. The bite‐out condition contains high dust density and smaller electron density. From simulation results in comparatively strong bite‐out conditions, we found that the ion effects on conductivity become significant with smaller dust size, lower electron temperature, and lower neutral density. For comparatively weak bite‐out conditions, the ion effects on conductivity become significant with larger dust size, higher electron temperature, and higher neutral density. On the other hand, for different dust sizes, electron temperatures and neutral density, the ion effects on complex permittivity become significant only in very strong bite‐out conditions. Based on these simulation results, we conclude that, in the absence of electron bite‐out conditions, the effect of ions on complex conductivity and permittivity is not significant and can be ignored. However, during bite‐out conditions, the effect of ions becomes significant and cannot be ignored because it significantly changes the conductivity and permittivity of dusty plasmas. Key Points: At PMSE (polar mesosphere summer echoes) altitudes, the bite‐out condition contains high dust and low electron density. In the absence of the bite‐out condition, the ion effects on conductivity and permittivity are not significant. In the presence of the bite‐out condition, the ion effects on conductivity and permittivity are significant and cannot be excluded.